Effect of Nanosecond Laser Beam Shaping on Cu(In,Ga)Se-2 Thin Film Solar Cell Scribing - Kuk, Seungkuk; Wang, Zhen; Jia, Zian; Zhang, Tao; Park, Jong-Keuk; Kim, Won Mok; Wang, Lifeng; Jeong, Jeung-hyun; Hwang, David J. (AMER CHEMICAL SOC, 2019)
The Cu(In,Ga)Se-2 (CIGS) thin film solar cell is a promising material architecture considering its high photovoltaic (PV) efficiency at low material cost. Recently, the authors demonstrated all laser based mini-module fabrication on a transparent conducting oxide (TCO) based CIGS architecture, using a cost-effective nanosecond laser beam illuminated from the transparent glass substrate side. While indium tin oxide (ITO) is a promising TCO to this end, allowing ohmic contact with CIGS and low sheet resistance, it suffers from unwanted damage upon laser scribing based on its preferred thickness of similar to 200 nm. Therefore, in this study, we investigate the effect of laser beam size and shape on ITO damage during P2 laser scribing. Although use of an enlarged laser spot could mitigate the damage issue, larger scribing width increased the dead zone. Thus, we have implemented the elliptical laser beam shaping technology so that a longer beam axis can suppress the ITO damage also maintaining high scribing speed while a shorter beam axis dictates narrow scribing width. Based on theoretical and numerical analyses, the ITO damage free scribing trend by enlarged laser beam, at least along one laser beam axis, is attributed to the buckling mechanism that facilitates film failure by enlarged laser beam. Transient thermo-mechanical modeling results imply that larger laser beam induced thermal stress will reach the film failure threshold earlier within laser pulse duration at lower interfacial temperature. However, further time-resolved experimental investigations are necessary to find the exact film delamination timing in conjunction with possible contribution of a microexplosion mechanism.
Keywords: CONDUCTING OXIDE BACK